2004
DOI: 10.1111/j.1728-4457.2004.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Religion as a Determinant of Economic and Demographic Behavior in the United States

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
277
0
11

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(299 citation statements)
references
References 65 publications
11
277
0
11
Order By: Relevance
“…In the United States, the role of religion for outcomes such as marriage, fertility, women’s labour force participation, education, and wages has been widely documented (Lehrer, 2004). In the context of India, there has been considerable discussion among demographers on the role of religion in explaining aggregate differences in fertility and child mortality between Hindus and Muslims (Dharmalingam & Philip Morgan, 2004; Guillot & Allendorf, 2010; Jeffery & Jeffery, 2002; Philip, Stash, Smith, & Mason, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, the role of religion for outcomes such as marriage, fertility, women’s labour force participation, education, and wages has been widely documented (Lehrer, 2004). In the context of India, there has been considerable discussion among demographers on the role of religion in explaining aggregate differences in fertility and child mortality between Hindus and Muslims (Dharmalingam & Philip Morgan, 2004; Guillot & Allendorf, 2010; Jeffery & Jeffery, 2002; Philip, Stash, Smith, & Mason, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, religious institutions often use strategies to promote childbearing (Lehrer 2004;McQuillan 2004;Morgan 1996;Wilcox, Chaves, and Franz 2004), as some church leaders influence daily behavior of members through broadcasted norms and ensuing "sanctions ranging in format from guilt to damnation" (Lesthaeghe and Surkyn 1988, 13). Indeed, frequency of church attendance, regardless of denomination, is a strong predictor of an individual's preference for families of three or more children (Hayford and Morgan 2008;Lesthaeghe and Surkyn 1988).…”
Section: The Social Capital Of Children and Religionmentioning
confidence: 99%
“…Traditionally, most fertility studies involving religious influence have addressed the differences between Catholics and Protestants, as Catholics tended to have larger families; but currently, this gap is almost nonexistent due to later marriage by Catholics (resulting in fewer children) and larger families of Protestants who attend church frequently (Lehrer 2004;McQuillan 2004;Mosher, Williams and Johnson 1992). More recent studies focus on the fertility differentials between mainline and evangelical Protestants, mostly attributed to doctrinal 5 differences of evangelicals espousing stronger pronatalist views (be fruitful and multiply) and an aversion to contraceptives and abortion (playing God) (Marcum 1981;McQuillan 2004).…”
Section: The Social Capital Of Children and Religionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study findings showed that Muslims with high level of dominant society immersion were exposed to the most ethnic and religious discrimination. Strikingly, Lehrer (2004) posited that religious affiliation might be a significant indicator of economic and demographic outcomes in American culture and therefore, religious involvement in the dominant belief system (Christianity) has usually crucial effects on health and economic well-being. Similarly, parents' ethnic-racial and religious socialization practices play a role in transmission of information, values, and perspectives about ethnicity, race, and religion to their children.…”
Section: Introductionmentioning
confidence: 99%